Transcriptomic and Functional Analysis of Two-Component Systems AdeRS, BaeRS, GacAS in Acinetobacter baumanniiAB5075 - Sulimani, Maha Mohammed (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2026)
Antimicrobial resistance constitutes one of the most significant global health challenges of our era, with Acinetobacter baumannii becoming a key priority pathogen owing to its extraordinary capacity to withstand various classes of antibiotics. A primary factor contributing to this resilience is the function of regulatory proteins, especially Two-Component Systems (TCSs), which allow the bacterium to detect environmental cues and swiftly modify gene expression. Nevertheless, the overarching regulatory networks of these systems are still not well comprehended. The objective of this thesis was to examine the regulatory functions of specific two-component systems (TCSs) AdeRS, BaeRS, and GacSA in A. baumannii AB5075, as well as to investigate their roles in antimicrobial resistance and various adaptive phenotypes. Through transcriptomic analysis (RNA-seq), I detected genome wide expression alterations in mutant strains that lacked these regulators when compared to the wild-type during exponential and stationary growth phases. Phenotypic assays, which included minimum inhibitory concentration (MIC) determination, disk diffusion, phenotypic microarrays and growth assays, were conducted to establish a correlation between transcriptional changes and antibiotic susceptibility and metabolism. In order to delve deeper into gene regulation, transcriptional start sites (TSSs) were delineated through differential RNA-seq, which facilitated the identification of promoter motifs and offered insights into the structure of transcriptional regulation in A. baumannii. Moreover, chromatin immunoprecipitation coupled with sequencing (ChIP-seq) was utilized to comprehensively map the binding sites of essential transcription factors (AdeR, BaeR, and GacA), uncovering their direct regulons and preferences for DNA binding. The results outlined in this thesis enhance our comprehension of TCS mediated regulation in A. baumannii. They reveal that AdeRS, BaeRS, and GacSA are responsible not only for the regulation of antibiotic resistance factors but also for affecting wider physiological mechanisms that aid in bacterial survival and adaptation. A comparative transcriptomic analysis of the adeRS, baeRS, and gacSA two-component systems has unveiled distinct regulatory effects on gene expression in Acinetobacter baumannii AB5075. Both adeR and adeS mutants exhibited numerous transcriptional alterations, particularly a downregulation of the adeABC efflux pump genes, thereby confirming their involvement in the regulation of antibiotic resistance. In the baeRS system, baeS demonstrated a more extensive transcriptomic influence compared to baeR, especially under the Late Stationary Phase LSP condition, where baeR was found to regulate only two genes. The gacA and gacS mutants revealed the highest number of differentially expressed genes across all systems, with gacA notably regulating the small RNAs sRNA100 and sRNA99, as indicated by peaks observed in chip seq data. The phenotypic characterization conducted through KirbyBauer disk diffusion assays indicated that all adeRS, baeRS, and gacSA mutants displayed measurable inhibition zones against specific antibiotics, implying partial changes in their susceptibility profiles. Nevertheless, minimum inhibitory concentration (MIC) testing revealed that these mutants continued to exhibit resistance, suggesting that although the regulatory disruptions influenced gene expression, they were not adequate to completely undermine the antibiotic resistance phenotypes. Differential RNA-seq analysis has revealed a total of 9,428 transcription start sites (TSSs) throughout the A. baumannii AB5075 genome, thereby creating a detailed map of promoter regions. This dataset serves as a crucial resource for comprehending transcriptional regulation and provides valuable insights into the potential role of two-component systems in modulating gene expression at the promoter level. To ascertain the genome-wide binding profiles of the response regulators AdeR, BaeR, and GacA, chromatin immunoprecipitation followed by sequencing (ChIP-seq) was employed. AdeR demonstrated a pronounced binding peak in the intergenic region situated between adeR and adeA, which aligns with its function in the regulation of the adeABC efflux operon. GacA displayed unique binding peaks linked to sRNA100, sRNA99, and sRNA91, reinforcing its role in post-transcriptional regulation via small RNAs. BaeR revealed a notable binding site located between fabR (ABUW_RS05395) and ABUW_RS05400, indicating a potential novel regulatory connection between fatty acid metabolism and stress response mechanisms.
APPROVED
Keywords: Acinetobacter baumannii; Two-Component Systems; adeRS; baeRS; gacAS